Prevalence of pregnancy induced thyroid disorders, diabetes and hypertension in a tertiary care teaching hospital: an observational study - Mummalaneni, Gowthami; Narasingarao, Tamaraba; Myneni, Krishna Kumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy induced thyroid disorders, gestational diabetes mellitus (GDM) and gestational hypertension are common problems in women with gestational period. Published literate shows wide range of prevalence in pregnancy induced disorders in other states of India, and as of now the exact prevalence in our study population is not studied. Hence, there present study was aimed to know the prevalence of pregnancy induced disorders in pregnant women in South Indian population. Methods: A total of 120 subjects were followed-up at the time of recruitment to entire gestational period. Standard guidelines were followed for the assessment of thyroid hormone levels, glucose tolerance test (OGTT) and blood pressure values at different intervals and positions. Apart from detailed clinical history has been taken and routine basic and obstetrical investigations were done. Results: Prevalence of thyroid dysfunction (15.0%), gestational diabetes mellitus (11.7%) and gestational hypertension (9.2%) was reported in the present study population. Subclinical hypothyroidism was highest prevalence amount thyroid disorders. Gestational diabetes subjects have mean blood glucose levels of 230.68±17.48 mg/dL with OGTT test. Gestational hypertensive patients had SBP of 152.4±10.8 and DBP of 96.6±6.4; pre-hypertensive subjects had SBP of 134.2±5.48 and DBP of 6.8±4.6 respectively. Conclusions: Our study findings were slightly higher than normal prevalence’s which are reported earlier by various authors. We suggested that early screening, diagnosis and treatment are warranted for the prevention of maternal and fetal complications in Indian population.